3D numerical and experimental modelling of multiphase flow through an annular geometry applied for cuttings transport. (June 2022) - Ferroudji, Hicham; Rahman, Mohammad Azizur; Hadjadj, Ahmed; Ofei, Titus Ntow; Khaled, Mohamed Shafik; Rushd, Sayeed; Gajbhiye, Rahul Narayanrao
Highlights: Parametric study of various drilling parameters on cuttings transport for vertical, deviated, and horizontal wellbores. Flow loop system for comparison of the obtained numerical results with the collected experimental data. Electrical Resistance Tomography (ERT) was considered to validate the numerical model (volume fraction of solid particles). Non-dimensionless analysis was carried out to estimate solid particles volume fraction and pressure drop gradient. Abstract: Accurate estimation of volume fraction and pressure gradient is considered indicating parameters of efficient cuttings transportation. It is vital, in this regard, to consider all parameters that can affect cuttings volume fraction and pressure drop during enrollment of the drilling process. The analysis was conducted based on the turbulent flow of a power-law fluid through an annular domain by employing the Finite Volume Method. In addition, dimensional relationships were developed with the Buckingham-π theorem. Before carrying out simulations, the numerical schemes were validated using actual measurements made with the flow loop system available in Texas A&M University at Qatar. The simulation results demonstrated the followings: (i) using a power-law type drilling fluid with a shear-thinning character would reduce energy consumption for an inclination greater than 45°; (ii) inclination angles from 45° to 60° would be least desirable for an effective cuttings transportation with a turbulent Ostwald-de Waele fluid. Graphical Abstract: Image, graphical abstract